2013
DOI: 10.1038/ki.2012.485
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of the relation between body mass index and short-term donor outcome of laparoscopic donor nephrectomy

Abstract: In this era of organ donor shortage, live kidney donation has been proven to increase the donor pool; however, it is extremely important to make careful decisions in the selection of possible live donors. A body mass index (BMI) above 35 is generally considered as a relative contraindication for donation. To determine whether this is justified, a systematic review and meta-analysis were carried out to compare perioperative outcome of live donor nephrectomy between donors with high and low BMI. A comprehensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 57 publications
0
26
1
1
Order By: Relevance
“…[24] Especially in the case of extended criteria donors, long-term follow-up data is lacking, as these donors have been increasingly accepted in the last decade. We know that donors with overweight/obesity,[25] and donors with vascular multiplicity have good short-term outcome. [2628] However, regarding other extended criteria, there is still a lot of uncertainty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24] Especially in the case of extended criteria donors, long-term follow-up data is lacking, as these donors have been increasingly accepted in the last decade. We know that donors with overweight/obesity,[25] and donors with vascular multiplicity have good short-term outcome. [2628] However, regarding other extended criteria, there is still a lot of uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…From earlier studies we know that outcome of both lean as overweight/obese donors are comparable. [3,29] Some centres accept minors as potential donors, which is an interesting phenomenon, as current guidelines state that minors should only be considered as potential donors if no other options exist, mostly in case of identical twins. There seems to be no reluctance in accepting a woman of childbearing age for kidney donation, which is in line with the Amsterdam Forum criteria, stating that donor nephrectomy is not detrimental to the prenatal course or outcome of future pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Several small retrospective studies have shown that there is no increased risk of deterioration in renal function in obese patients who donate a kidney during the first 5 years after surgery. [27][28][29] However, the follow-up duration was short, and these studies all concluded that overweight and obese kidney donors need intensive preoperative education and postoperative health maintenance. On the other hand, a recent cohort study of over 95 000 patients who underwent living-donor nephrectomy for kidney transplant demon strated an increased risk of end-stage renal disease over a median 7.6 years versus that shown in matched healthy nondonors.…”
Section: Discussionmentioning
confidence: 99%
“…Morbidly obese people currently account for <5% of the total living kidney donor pool , and are potential candidates to reverse the downward trend in living donation. Morbid obesity, however, is a contraindication for living kidney donation at most U.S. transplant centers due to concerns for an increase in perioperative complications and the known contribution of obesity to the development of chronic kidney disease and its risk factors such as hypertension (HTN) and type 2 diabetes . Bariatric surgery has been shown to provide long‐term weight loss and reverse obesity‐associated medical comorbidities , and could represent a solution to transform morbidly obese people into viable living kidney donor candidates.…”
Section: Introductionmentioning
confidence: 99%